Morfometría geométrica de la superficie oclusal de dientes de lirones (Gliridae, Rodentia, Mammalia): estudio preliminar, problemas y posibles aplicaciones. - García Paredes, Israel (Coloquios de Paleontología, 2003)
A preliminary work to test the landmark-based geometric morphometrics methods for the study of dental crown pattern of upper cheek teeth of glirids or dormouse (Gliridae, Rodentia, Mammalia) is presented. As an example, a sample of the fossil especies Armantomys jasperi DAAMS, 1990 M1 and M2 has been studied. There are 22 landmarks defined in its oclusal surface. The experimental design that allows the landmarks identification and the comparision of diferents specimens by superimposition methods has been done. A cluster analysis test the capacity of the refered method to distinguish between M1 and M2. A discriminant analysis give the percentage success in prediction in the two upper molars groups. This study allow a satisfactory separation of M1 and M2 and the identification of a mistake in one specimen.
Keywords: Gliridae (Rodentia; Mammalia); Geometric morphometrics; Landmarks; Upper cheek teeth; Oclusal surface; Experimental design; Superimposition methods; Cluster analysis; Discriminant analysis